Pengaruh Fraksinasi Kromatografi Cair Vakum terhadap Kandungan Fenolik, Flavonoid, dan Aktivitas Penghambatan α-Glukosidase Daun Nangka (Artocarpus heterophyllus Lam.): - - Istiara Subekti; Tanti Azizah Sujono; Andi Suhendi; Arifah Sri Wahyuni; Aditya Naova Sofyan (Journal of Pharmaceutical and Sciences, 2026)
Artocarpus heterophyllus Lam leaves are recognized as a promising source of bioactive compounds with potential antidiabetic activity. This study aimed to evaluate the effects of vacuum liquid chromatography (VLC) fractionation on the distribution of phenolic and flavonoid compounds and their α-glucosidase inhibitory activity. Crude ethanolic extract was fractionated by VLC into polar, semipolar, and nonpolar fractions. Total phenolic content (TPC) and total flavonoid content (TFC) were determined using the Folin–Ciocalteu and aluminum chloride colorimetric assays, respectively, while α-glucosidase inhibitory activity was evaluated using a p-nitrophenyl-α-D-glucopyranoside-based assay. The crude extract exhibited the highest TPC (4.70 ± 0.37 mg GAE/g extract) and TFC (5.63 ± 0.11 mg QE/g extract), whereas both parameters decreased markedly after fractionation. Consistently, the crude extract showed the strongest α-glucosidase inhibitory activity, as indicated by the lowest IC₅₀ value, while the nonpolar fraction exhibited the weakest activity. These findings demonstrate that VLC fractionation redistributed rather than enhanced the bioactive constituents responsible for α-glucosidase inhibition. The crude extract therefore represents a promising natural source of α-glucosidase inhibitors and supports the potential utilization of Artocarpus heterophyllus Lam for the development of plant-derived antidiabetic agents.